Adequacy of low-cost housing: A study of the people’s housing programme (PHP) at Kuala Lumpur / Wan Sumayyah Syahidah Wan Mohamad, Noor Amira Syazwani Abd Rahman and Mohd Rozaimy Ridzuan - Wan Mohamad, Wan Sumayyah Syahidah; Abd Rahman, Noor Amira Syazwani; Ridzuan, Mohd Rozaimy (Universiti Teknologi MARA Cawangan Pahang, 2019)
The low cost housing is one of the contemporary challenges of most developing countries and it is assumed to be a perennial problem in some of these countries due to rapid population growth and urbanization. The adequacy, affordability and quality of houses are highlighted in the Eleventh Malaysian Plan (2016-2020). It reflects the political will of the government in elevating the standard of living of the citizens. This paper examines the adequacy of low-cost housing standards (public facilities, flat features, and social environment) among People’s Housing Programmes (PHP) residents. The scope of this study pertains to the residents of PHP Kampung Limau, Pantai Dalam, Kuala Lumpur. The methodology employed in this research was cross-sectional by applying the convenience sampling technique for the identification of the units of analysis. The findings of the study show that the majority of the beneficiaries of low-cost housing programmes scored high mean for all the independent variables in this study. It is hoped that this study can be used as a yardstick to adopt new strategies as well as improving new building standards for low-cost housing, particularly in Malaysia and developing countries at large.